Delayed Healing of Traumatic Ulcers Due to Toothpicks Injuries Exacerbated by Psychological Stress in Teledentistry Patients - Puspitasari, Yeni; Anjani, Khamila Gayatri; Zulkarnain, Hakim; Dian Artanty (Babali Publisher, 2024)
Background: A traumatic ulcer is a mucosal lesion caused by direct physical, mechanical, thermal, or chemical trauma to the mucosa, such as from malocclusion, ill-fitting dentures, or bad habits like using toothpicks. Treatment aims to alleviate pain, eliminate the primary source of trauma, and promote healing of the ulcer. The objective of this case report is to document traumatic ulcers resulting from mechanical trauma exacerbated by stress. Case Report: A male patient presented with an ulcer that had been present for three weeks after accidentally injuring himself with a toothpick. The ulcer had not been treated previously. The patient reported experiencing high levels of stress and sleep deprivation due to working on his thesis. Clinical photos provided by the patient revealed a solitary, white-to-yellowish ulcer, approximately 5x3 mm in size, on the left lateral side of the tongue. The patient was prescribed an antiseptic anti-inflammatory aloe vera extract gel via teledentistry. Discussion: Under stress, the HPA axis releases corticotropin-releasing hormone (CRH) from the hypothalamus, activating the adrenal cortex to release glucocorticoids. The interaction between glucocorticoids and proinflammatory cytokines is a physiological mechanism that links stress and wound healing. Glucocorticoids can interfere with the inflammatory response and reduce white blood cell activity, thereby affecting wound healing. Conclusion: Traumatic ulcers can be exacerbated by psychological conditions such as stress. Dentists and healthcare providers should conduct thorough patient history assessments, clinical examinations, and provide appropriate therapy and oral health education to promote effective ulcer healing.